A survey of kindergarten teachers' perception of children's literacy acquisition and classroom learning materials - Chang, Susan Yu Shieng (Universiti Malaysia Sarawak (UNIMAS), 2007)
The main purpose of this study was to investigate kindergarten teachers' perceptions of children's literacy acquisition and the learning materials used in fostering literacy development. 50 preschool teachers have participated in this study. From this number of respondents, 16 teachers were randomly selected for the purpose of finding out the types of learning materials used in classroom. Basically, two perspectives of literacy acquisition were investigated in this study: Reading Readiness perspective and Emergent Literacy perspective. Reading readiness is a concept stresses on "waiting" until a child is ready to learn to read before providing them any instruction. Emergent literacy, on the other hand, stresses on creating an environment which is rich in print. In this study, there were more teachers who upheld Reading Readiness perspective than those who advocated for the Emergent Literacy perspective as well as those grouped into "others". From the classroom observation, Reading Readiness materials such as alphabet books, flashcards, commercialised/teacher made on-wall pictures and copying wordlist were frequently used in these institutions. Apart from that, Emergent Literacy materials like story books, theme-related books, reading aloud materials, authentic print-related props and literature props were also utilized in majority of these kindergartens. The results indicated that teachers' use of learning materials reflected their perceptions of children's literacy acquisition.